Choice- and trial-history effects on causality perception in Schizophrenia Spectrum Disorder - Kai Streiling; Rasmus Schülke; Benjamin Straube; Loes C. J. van Dam (Schizophrenia)
Abstract Perceiving causality is a low-level, immediate cognitive process based on temporal and spatial cues relating to sensory events and could be viewed as a perceptual judgement. Perceptual judgements in general are affected by a choice- and trial history bias, however, it is not yet fully understood how such a bias integrates into the perception of causality. Here, we investigate judgements of perceptual causality in Schizophrenia Spectrum Disorder (SSD) as a perceptual decision process with systematic influences from past choices and experiences. We analysed previously collected data from a causality-judgement experiment using Michotte launching events and examined differences between patients with SSD (SSDs) and healthy control participants (HCs). We did this on several levels to shed light on known dysfunctions in the judgement of cause-effect relations in SSD, such as the jumping-to-conclusions bias. Using multiple Generalized Linear Mixed-Effects Models (GLMMs) revealed a significant direct influence of the choice-history for both participant groups. Trial-history (previous stimulus experiences) on the other hand appears to exert a more subtle influence on the current choice by modulating the effect of choice-history and current spatial and temporal properties. Regarding the stimulus of a given trial, SSDs relied more on spatial properties and less on temporal properties than HCs. Furthermore, an analysis of effects across time suggested an increasing reliance on previous choices for SSDs, and a decreasing effect for HCs. This hints towards a potentially maladaptive pattern which might contribute to biased causal attributions in SSD.